The relationship between the physical activity efficacy and physical activity of the middle school students - ALPKAYA, UFUK (IERMAKOV S S, 2019)
Purpose:The purpose of this study is to determine the physical activity efficacy and physical activity of the middle school students, according to gender and to analyze the relationship between them. Material: The study group consisted of a total of 701 students from three public secondary schools, 343 of whom were female and 358 were male students. In order to determine the physical activity efficacy of the students, the Physical Activity Efficacy Scale was used, while the Physical Activity Questionnaire for Older Children was used for establishing the level of physical activity. In evaluating the data, descriptive statistics, independent t-test, Pearson correlation tests were used as statistical methods. Results: According to the data obtained by the study, the students'physical activity efficacy was found to be good, with no difference between the females and the males (p>0.05). The students' physical activity level was average, while the males were found to be physically more active than the females (p<0.05). A positive correlation was found between the physical activity efficacy and the physical activity of the students (p<0.05). Conclusions: According to the findings of this study, physical activities should be increased during the time of the middle school, which is a part of the period of adolescence. Besides, in order to enhance their physical activity efficacy, the adolescents should be provided with physical activity environments.
Keywords: adolescence; physical activity efficacy; physical activity; middle school; gender; ACTIVITY SELF-EFFICACY; GENDER-DIFFERENCES; HEALTH-PROMOTION; BODY-MASS; EXERCISE; DETERMINANTS; CHILDREN; ADOLESCENTS; ACHIEVEMENT; MOTIVATION